ANALISIS PERHITUNGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 PADA PT INTRACO PENTA PRIMA SERVIS (IPPS) - Padja, Aditya Rachman; Tinangon, Jantje J.; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Income Tax Article 21 is Tax withheld by others on income in the form of salaries, wages, honoraria, allowances, and other payments by the name and in any form in connection with employment, services, or activities undertaken by individual taxpayers in the country. On this basis, the Office of Government Agencies that hire or permanent employee is obliged to withhold, deposit, and report of Income Tax Article 21 on income received by employees every month through the Tax return period. This research was conducted in PT Intraco Penta Prima Servis (IPPS), The purpose of this research was conducted is to determine whether the calculation, remittance, and Article 21 of the Income Tax Reporting at PT Intraco Penta Prima Services (IPPS) if it is in accordance with Law No.36 Year 2008 on Income Tax. This study used descriptive research methods, and data collection technique used is the technique of interview, and documentation. The results of this study indicate that the application of the calculation, remittance, and Article 21 of the Income Tax Reporting by PT Intraco Penta Prima Services (IPPS) in accordance with Act 36 of 2008 on Income Tax, and is also expected that the tax authorities should provide more socialization of Income Tax Article 21 taxpayers, especially acting as a cutter or a tax collector that does not happen anymore mistakes in calculations.